(z+j(z-j)(z+1) experiment

This commit is contained in:
Robin. P. Clark 2019-09-10 09:27:29 +01:00
parent 5d5a2cb72f
commit 38d2a276e7

View File

@ -193,11 +193,12 @@ int zero_only_2 ( int input )
static int x0,x1,x2,x3,x4; static int x0,x1,x2,x3,x4;
int res; int res=1500*4;
// (z^2+1)^2 // (z^2+1)^2 ZEROS AT HALF NYQUIST
// z^4 z^2 1 // z^4 z^2 1
res = input + 2*x2 + x4; //res = input + 2*x2 + x4;
x4 = x3; x4 = x3;
x3 = x2; x3 = x2;
@ -215,12 +216,16 @@ int zero_only_3 ( int input )
static int x0,x1,x2,x3,x4; static int x0,x1,x2,x3,x4;
static int x5,x6,x7,x8,x9; static int x5,x6,x7,x8,x9;
int res; int res=1500;;
// (z^2+1)^3 // (Z+j)(Z-j) == (Z^2+1) // zero at nyquist
// (z^2+1)^3 ZEROS AT HALF NYQUIST
// z^6 z^4 2z^3 z^2 2*z 1 // z^6 z^4 2z^3 z^2 2*z 1
res = input + x2 +2*x3 + x4 +2*x2 + x6; //res = input + x2 +2*x3 + x4 +2*x2 + x6;
// (Z^2 - 1)(Z+1) is zero at half nyquist and zero at nyquist
// z^3 +z^2 + z + 1
res = input + x1 + x2 + x3;
x8 = x7; x8 = x7;
x7 = x6; x7 = x6;
x6 = x5; x6 = x5;
@ -230,7 +235,7 @@ int zero_only_3 ( int input )
x2 = x1; x2 = x1;
x1 = input; x1 = input;
return res/8; return res/4;
} }
int zero_only_4 ( int input ) int zero_only_4 ( int input )
@ -239,10 +244,14 @@ int zero_only_4 ( int input )
static int x0,x1,x2,x3,x4; static int x0,x1,x2,x3,x4;
static int x5,x6,x7,x8,x9; static int x5,x6,x7,x8,x9;
int res; int res=1500*16;
// (Z^2+1)^4 ZEROS AT HALF NYQUIST
// z^8 2z^6 2z^5 2z^4 4z^3 2z^2 2z^1 + 1 // z^8 2z^6 2z^5 2z^4 4z^3 2z^2 2z^1 + 1
res = input + 2*x2 +2*x3 + x4 + 4*x5 + 2*x6 + 2*x7 + x8; //res = input + 2*x2 +2*x3 + x4 + 4*x5 + 2*x6 + 2*x7 + x8;
// (Z+1)(Z-1 // zero at nyquist zero at half nyquist
// (Z^2 - 1)
//
x8 = x7; x8 = x7;
x7 = x6; x7 = x6;
x6 = x5; x6 = x5;